Adequate reporting of the sample size calculation in surgical randomized controlled trials - Speich, B (Elsevier, 2019)
Background: The sample size calculation for a randomized controlled trial should assure that a statistically significant and clinically relevant difference can be detected with a high probability. To be certain that readers of a randomized controlled trial can critically judge whether the assumptions for the sample size calculation were realistic, a number of specific subitems should be reported. Methods: In this minireview, the frequency of adequate reporting of specific sub-items of the sample size was assessed from surgical randomized controlled trials that were published in the 5 leading general surgical journals in 2017. Subitems from the Consolidated Standards for Reporting Trials and from the Standard Protocol Items: Recommendations for Interventional Trials Statement were considered. Results: A total of 85 relevant randomized controlled trials were identified over PubMed. The overall adequate reporting of the sample size according to the Consolidated Standards for Reporting Trials was 53% (45 of 85). When considering additional subitems from the Standard Protocol Items: Recommendations for Interventional Trials Statement which are not explicitly requested by the Consolidated Standards for Reporting Trials Statement, the adherence decreased to 12% (10 of 85). Conclusion: The adherence in reporting potentially important subitems of the sample size from the Consolidated Standards for Reporting Trials Statement was moderate among surgical randomized controlled trials. It is crucial that surgeons who plan and conduct randomized controlled trials be aware of these subitems.